2020
DOI: 10.1360/n112018-00293
|View full text |Cite
|
Sign up to set email alerts
|

Research progress and development trend of cross-layer energy efficiency optimization in data centers

Abstract: Cross-layer optimization in ultra wideband networks Science in China Series F-Information Sciences 50, 760 (2007); Cross-layer transmission and energy scheduling under full-duplex energy harvesting wireless \\OFDM joint transmission SCIENCE CHINA Information Sciences 59, 102310 (2016); Cross-layer packet scheduling for downlink multiuser OFDM systems Science in China Series F-Information Sciences 52, 2369 (2009); Model-based cross-layer monitoring and adaptation of multilayer systems SCIENCE CHINA Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several noteworthy investigations have yielded significant insights among these. The study undertaken by Wang et al (2020) delved into the comprehensive examination of artificial intelligence (AI) applications in the realms of conflict prediction and prevention. The study underscores the potential of machine learning algorithms in the analysis of historical data and the simulation of war scenarios.…”
Section: Literature Review Of Existing Methods and Models For Data-dr...mentioning
confidence: 99%
“…Several noteworthy investigations have yielded significant insights among these. The study undertaken by Wang et al (2020) delved into the comprehensive examination of artificial intelligence (AI) applications in the realms of conflict prediction and prevention. The study underscores the potential of machine learning algorithms in the analysis of historical data and the simulation of war scenarios.…”
Section: Literature Review Of Existing Methods and Models For Data-dr...mentioning
confidence: 99%
“…For data center refrigeration, heating, ventilation, air conditioning (HVAC), and computer room air conditioning (CRAC) are commonly applied, and many experiments and models have been developed for the accurate estimation of these processes. Some researchers have found that the overall consideration of the IT system layer and the use of a supporting facility layer for cross-layer optimization can maximize the energy-saving potential of the data center [ 22 , 23 ]. This research focused on the cross-layer energy consumption optimization of the data center, taking the modules as a whole and considering the relationships between modules and carrying out unified optimal scheduling and management.…”
Section: Related Workmentioning
confidence: 99%
“…A considerable amount of literature has been published on reducing PUE, focusing on optimizing the DC design and location (Yue et al., 2018), job scheduling of IT facility (Beloglazov & Buyya, 2012; Jing‐Yu et al., 2019), decentralized power allocation schemes (Bistritz et al., 2019; Miller et al., 2015; Zhou & Bambos, 2015), air management systems (Fouladi et al., 2017), cooling systems (Hossain et al., 2017), etc. In recent years, the cross‐layer energy efficiency optimization methods have been studied, which include the cooling optimization via IT scheduling, power distribution optimization via IT scheduling, joint optimization of IT and cooling, and joint optimization of IT and power distribution (Wang et al., 2020). The cross‐layer methods aim at improving the power supply system efficiency with IT load dispatching and the combined efficiency improvement of the IT and cooling systems.…”
Section: Energy Efficiency Of Data Centersmentioning
confidence: 99%